Gradient sintering and micro-valve effect-based high-self-opening-rate stuffing sand and preparation method thereof
By designing a gradient sintering structure and a micro-valve effect for the guiding sand, the contradiction between impermeability and castability of the guiding sand is resolved, achieving high self-opening rate and low stress start-up, which is suitable for the preparation of high-oxygen steel and clean steel.
Patent Information
- Application Number
- CN202511535952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-27
- Publication Date
- 2026-01-13
AI Technical Summary
There is a contradiction between the existing diversion sand and its impermeability and its ability to be poured, making it difficult to achieve a high self-opening rate at the same time. Traditional chemical formula optimization cannot effectively solve this contradiction.
The gradient sintering structure design includes a dense sealing layer, a weak bonding transition layer, and a loose maintenance layer. High-hardness inert microspheres are introduced into the weak bonding transition layer to form a micro-valve effect, thereby achieving stress concentration and crack initiation.
It significantly improves the self-opening rate of the diversion sand, reduces the starting force for pouring, ensures the smooth diversion of molten steel at high temperatures, and maintains a self-opening rate of over 99.4%, demonstrating strong performance stability and adaptability.
Smart Images

Figure CN121318489A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of functional refractory materials for metallurgical continuous casting, in particular to a high self-opening rate drainage sand based on gradient sintering and micro-valve effect and a preparation method thereof. BACKGROUND
[0002] The self-opening rate of the ladle drainage sand is a key comprehensive index for measuring whether the continuous casting production can be efficient and smooth, which directly affects the production rhythm, molten steel quality, operation safety and production cost. At present, the technical improvement in the industry generally focuses on optimizing the performance of the drainage sand by adjusting the chemical composition of the drainage sand, such as precisely controlling the proportion of main materials such as chrome ore sand and quartz sand, or changing the type and amount of sintering agents (such as feldspar, borax, etc.), the core purpose of which is to improve the sintering behavior of the material under the action of high-temperature molten steel.
[0003] However, this traditional method based on formula adjustment has an inherent fundamental contradiction. On the one hand, in order to effectively resist the static pressure and slag erosion of high-temperature molten steel, prevent the formation of a hard "cold steel" layer due to excessive penetration of molten steel, and form a sintered layer on the surface of the drainage sand as much as possible, the sintered layer must be as dense and hard as possible, with excellent impermeability. On the other hand, in order for the drainage sand to flow out smoothly and guide the molten steel during the start of casting, the sintered shell must be easily broken at the moment the slide gate is opened, with good openability. This inherent contradiction between "impermeability" and "openability" constitutes a deep technical paradox, which has resulted in the self-opening rate of existing drainage sand products being unable to achieve a qualitative leap, and even under the most optimal conditions, it is usually difficult to stably maintain at the ideal level of 99.5% or above. The existing technical path essentially seeks a fragile balance point between these two contradictions, which is a helpless compromise solution and cannot fundamentally coordinate and solve this contradiction.
[0004] Therefore, there is an urgent need in the art to introduce a completely new technical approach to break through the limitations of existing simple chemical formula optimization and completely solve the above-mentioned contradiction from the aspects of structural design and mechanism. SUMMARY
[0005] In view of the above problems, the present application provides a high self-opening rate drainage sand based on gradient sintering and micro-valve effect, and a preparation method thereof, which can specifically adopt the following technical solutions: The high self-opening rate drainage sand based on gradient sintering and micro-valve effect provided by the present application comprises a dense sealing layer, a weakly bonded transition layer and a loose maintenance layer arranged in sequence. The dense sealing layer comprises the following raw materials by weight: chrome iron ore sand 50-70, zircon sand 20-30, potassium feldspar powder 5-8, boron glass powder 2-4, high-purity graphite 2-3, and metal silicon powder 0.5-1. The weakly bonded transition layer comprises the following raw materials by weight: zircon sand 50-70, low-chromium magnesia 20-30, potassium feldspar powder 3-5, boron glass powder 2-3, inert microbeads 1-3, high-purity graphite 2-3, metallic silicon powder 0.5-1, and organic fiber 0.1-0.5. The loosely maintained layer comprises the following raw materials by weight: high-purity fused magnesia 97-99 and high-purity graphite 1-3.
[0006] Preferably, the chromite sand has Cr2O3≥45%, the zircon sand has ZrO2≥65%, the low-chromium magnesia has MgO≥90%, the high-purity fused magnesia has MgO≥99.50%, and the high-purity graphite has C≥99.99%.
[0007] Preferably, the potassium feldspar powder has a particle size of 200 mesh, the boron glass powder has a particle size of 200 mesh, the high-purity graphite has a particle size of 1000 mesh, the metallic silicon powder has a particle size of 200 mesh, the high-purity fused magnesia has a particle size of 20-180 mesh, and the organic fiber has a length of 1-3 mm.
[0008] Preferably, the inert microbeads are in a spherical or spheroidal structure made of zirconia, corundum, or boron nitride, have a Mohs hardness greater than 7, and have a particle size of 0.5-1 mm.
[0009] The preparation method of the high self-opening rate drainage sand based on gradient sintering and micro-valve effect comprises the following steps: In the first step, granular materials for the dense sealing layer, the weakly bonded transition layer, and the loosely maintained layer are prepared, specifically as follows: (1) Preparing granular materials for the dense sealing layer: chromite sand, zircon sand, potassium feldspar powder, boron glass powder, high-purity graphite, and metallic silicon powder are prepared in corresponding proportions, and a 40-45% yellow dextrin aqueous solution is prepared in an amount of 3-4% of the total mass of the above mixture; then, a stirring tank is started, and the chromite sand and zircon sand are first added, followed by the yellow dextrin aqueous solution, and stirring is performed for 3 minutes; then, the potassium feldspar powder and the boron glass powder are added to the stirring tank, followed by the high-purity graphite and the metallic silicon powder, and stirring is continued for 30 minutes to complete the granulation; finally, the materials in the stirring tank are transferred to a drying cylinder at 200-250°C, and drying is completed in an air atmosphere for 1-2 hours. (2) Preparation of weakly bonded transition layer granules: Prepare zircon sand, low-chromium magnesia sand, potassium feldspar powder, borosilicate glass powder, inert microspheres, high-purity graphite, metallic silicon powder, and organic fiber according to the corresponding proportions. Then, prepare water-based resin according to 2.5-3.5% of the total mass of the above mixture. Next, start the mixing tank, add zircon sand and low-chromium magnesia sand first, then add water-based resin, and stir for 3 minutes. After that, add potassium feldspar powder and borosilicate glass powder to the mixing tank, then add inert microspheres, high-purity graphite, metallic silicon powder, and organic fiber, and continue stirring for 30 minutes to complete granulation. Finally, transfer the material in the mixing tank to a drying drum at 200-250℃ and keep it in an air atmosphere for 1-2 hours to complete drying. (3) Preparation of loose maintenance layer granules: Prepare high-purity fused magnesia and high-purity graphite according to the corresponding proportions, and then prepare water-based resin according to 2.5-3.5% of the total mass of the above mixture; then, start the mixing tank, add high-purity fused magnesia first, then add water-based resin, and stir for 3 minutes; then, add high-purity graphite into the mixing tank and continue stirring for 30 minutes to complete granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, and keep it in an air atmosphere for 1-2 hours to complete drying; The second step involves laying the granular material obtained in step one at the bottom of the ladle, forming a loose maintenance layer, a weakly bonded transition layer, and a dense sealing layer, respectively. The loose maintenance layer accounts for 30% of the total height of the diversion sand, the weakly bonded transition layer accounts for 50% of the total height of the diversion sand, and the dense sealing layer accounts for 20% of the total height of the diversion sand.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Gradient sintered layer structure design – resolving the core contradiction For the first time, a functional gradient structure of "dense sealing layer - weakly bonded transition layer - loose maintenance layer" was constructed inside the diversion sand. This assigns "anti-permeability" and "easy-to-open" functions to different structural layers, fundamentally solving the technical challenge of traditional diversion sand's inability to simultaneously achieve sealing and pouring capability. Specifically, the dense sealing layer on the surface provides a high-strength seal, achieving a pressure resistance of 15-25 MPa at high temperatures, effectively preventing molten steel penetration. The weakly bonded transition layer in the middle layer forms a weak-strength zone with a pressure resistance of 8-15 MPa, providing conditions for low-stress initiation. The loose maintenance layer at the bottom maintains fluidity throughout, ensuring smooth pouring.
[0011] 2. Microvalve effect – achieving low-stress start-up High-hardness inert microspheres are introduced into the weakly bonded transition layer as "stress concentration points." The microspheres form a weak sintering interface with the matrix, becoming natural crack initiation points. Under the hydrostatic pressure of molten steel, this generates a "small force can move a large weight" stress concentration effect, guiding the directional propagation of cracks and significantly reducing the initiation force for casting. The initiation pressure for casting in this invention can be reduced by more than 40%, providing a key guarantee for achieving a near 100% self-initiation rate.
[0012] 3. Multifunctional Collaborative Enhancement System Antioxidant synergistic mechanism: Graphite and silicon powder in the dense sealing layer and weakly bonded transition layer form a SiC protective layer under high temperature conditions, which effectively prevents molten steel erosion and nodulation.
[0013] Ventilation channel mechanism: The organic fibers of the weakly bonded transition layer carbonize and decompose during use in high-temperature environments, forming a microporous network that provides a dedicated escape channel for the gas to escape during casting.
[0014] Synergistic effect: The above-mentioned "anti-blocking" (antioxidant) and "dredging" (ventilation) functions complement each other, producing a synergistic enhancement effect of "1+1>2".
[0015] 4. Optimized design of the binder system The dense sealing layer uses a yellow dextrin solution as a binder, which can improve the green strength of the granules before sintering and ensure the stability of the gradient structure of the guiding sand. Yellow dextrin decomposes at 300-500℃, which can avoid the formation of too much glass phase at high temperature and ensure the structural integrity of the dense layer.
[0016] Both the weakly bonded transition layer and the loosely maintained layer use water-based resin as a binder. In the weakly bonded transition layer, the flexibility of the resin polymer chains adapts to the difference in thermal expansion between the microspheres and the matrix, preventing interfacial cracking. The resin carbonization film and the microsphere interface form a synergistic mechanism of "weak bonding-strong guidance," without affecting the thermal decomposition behavior of the fibers or the formation of ventilation channels, thus achieving controllable weak bonding in the transition layer. Secondly, the water-based resin decomposes and carbonizes at 200-400℃, creating a weak interface between the weakly bonded transition layer and the loosely maintained layer.
[0017] The two binders described above undergo thermal decomposition at different temperatures, and their products complement each other, ultimately forming a continuous, bottom-up macroscopic bond strength gradient within the drainage sand. This gradient results in the lowest strength in the loose support layer and the highest strength in the dense sealing layer. This strength gradient, in conjunction with the "micro-valve effect," ensures that cracks can precisely initiate and propagate within the weakly bonded transition layer during initial casting, thus fundamentally resolving the contradiction between sealing performance and castability.
[0018] 5. Overall performance improvement The preparation method described in this invention has controllable raw material costs, high production efficiency, and a stable self-opening rate of ≥99.4% for the resulting guiding sand, with a batch-to-batch standard deviation of <0.1%. It is suitable for the preparation of high-quality steel grades such as high-oxygen steel and clean steel, and also has good effects on steel ladles used for more than 60 minutes. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the gradient sintered layer structure formed by the diversion sand in the ladle nozzle according to the present invention.
[0020] Figure 2 This is a schematic diagram of the crack propagation path of each layer of the diversion sand described in this invention under stress.
[0021] Figure 3 This is a schematic diagram of the crack propagation path under stress after the sintering of the diverting sand described in Comparative Example 2. Detailed Implementation
[0022] The embodiments of the present invention will be described in detail below. The embodiments are based on the technical solutions of the present invention and provide detailed implementation methods, but the protection scope of the present invention is not limited to the following embodiments.
[0023] The embodiments and comparative examples in this invention all use raw materials that meet the following standards: Chromite sand Cr2O3≥45%, zircon sand ZrO2≥65%, low-chromium magnesia MgO≥90%; The particle size of potassium feldspar powder is 200 mesh, the particle size of borosilicate glass powder is 200 mesh, the particle size of metallic silicon powder is 200 mesh, and the length of organic fiber is 1-3 mm. High-purity fused magnesia with MgO ≥ 99.50% and a particle size of 20-180 mesh; High-purity graphite C≥99.99%, particle size 1000 mesh; The inert microspheres are made of zirconium oxide, corundum, or boron nitride, and have a spherical or near-spherical structure. They have a Mohs hardness greater than 7 and a particle size of 0.5-1 mm.
[0024] The selection of the aforementioned raw material standards ensures the high-temperature stability, impermeability, and sintering controllability of the guiding sand. For example, high-purity chromite sand and zircon sand provide excellent high-temperature resistance, while high-purity graphite and metallic silicon powder help form a SiC protective layer to prevent oxidation.
[0025] Example 1: (1) Prepare the raw materials for the dense sealing layer according to the following weight parts: 62.4 chromite sand, 26 zircon sand, 5.5 potassium feldspar powder, 2.8 borosilicate glass powder, 2.5 high-purity graphite, and 0.8 metallic silicon powder; then prepare a 40% yellow dextrin aqueous solution according to 3.5% of the total mass of the above mixture; then start the mixing tank, add chromite sand and zircon sand first, then add yellow dextrin aqueous solution, and stir for 3 minutes; then add potassium feldspar powder and borosilicate glass powder to the mixing tank, then add high-purity graphite and metallic silicon powder, and continue stirring for 30 minutes to complete granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 2 hours to complete drying, and obtain dense sealing layer granules; (2) Prepare the raw materials for the weakly bonded transition layer according to the following weight proportions: 65 zircon sand, 25 low-chromium magnesia sand, 3.5 potassium feldspar powder, 2.0 borosilicate glass powder, 1.0 spherical zirconia microspheres, 2.5 high-purity graphite, 0.7 metallic silicon powder, and 0.3 polypropylene fiber (i.e., organic fiber); then prepare water-based resin according to 3% of the total mass of the above mixture; then start the mixing tank, add zircon sand and low-chromium magnesia sand first, then add water-based resin, and stir for 3 minutes; then add potassium feldspar powder and borosilicate glass powder to the mixing tank, then add spherical zirconia microspheres, high-purity graphite, metallic silicon powder and polypropylene fiber, and continue stirring for 30 minutes to complete granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 2 hours to complete drying, and obtain the weakly bonded transition layer granules; (3) Prepare the raw materials for the loose support layer according to the weight parts, including: 98.5% high-purity fused magnesia and 1.5% high-purity graphite; then prepare water-based resin according to 3% of the total mass of the above mixture; then start the mixing tank, add the high-purity fused magnesia first, then add the water-based resin, and stir for 3 minutes; then add the high-purity graphite into the mixing tank and continue stirring for 30 minutes to complete the granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 1 hour to complete the drying and obtain the loose support layer granules. (4) such as Figure 1 As shown, the above-obtained granular material is sequentially laid at the bottom of the ladle to form a loose maintenance layer, a weakly bonded transition layer, and a dense sealing layer, respectively. The loose maintenance layer accounts for 30% of the total height of the diversion sand, the weakly bonded transition layer accounts for 50% of the total height of the diversion sand, and the dense sealing layer accounts for 20% of the total height of the diversion sand.
[0026] (5) Conduct industrial trials: 500 heats were tested on a 200-ton ladle at a steel plant to smelt high-oxygen steel, with an average waiting time of 45 minutes.
[0027] The experimental results are as follows: 3 furnaces did not self-start, resulting in a self-start rate of 99.4%. Scanning electron microscopy revealed a uniform three-layer guide sand structure with a relatively clear gradient. The dense sealing layer formed a high-strength sintered shell, the weakly bonded transition layer contained micropores and weak interfaces, and the loose maintenance layer remained loose. During casting, cracks initiated from the inert microspheres in the weakly bonded transition layer and propagated along the gradient direction (e.g., ...). Figure 2 As shown in the figure, low-stress start-up is achieved.
[0028] Example 2: In this embodiment, when preparing the weakly bonded transition layer granules, the inert microspheres are spherical zirconia microspheres with a weight ratio of 2 parts, and the rest are the same as in Example 1.
[0029] The results of the industrial test are as follows: out of 500 furnaces, only 1 furnace failed to start automatically, resulting in a self-start rate of 99.8%.
[0030] Example 3: In this embodiment, when preparing the weakly bonded transition layer granules, the inert microspheres are spherical zirconia microspheres with a weight ratio of 3 parts, and the rest are the same as in Example 1.
[0031] The results of the industrial test are as follows: out of 500 furnaces, 2 furnaces did not start automatically, resulting in a self-start rate of 99.6%.
[0032] Comparative Example 1: (1) Prepare the raw materials for the dense sealing layer according to the following weight parts: 62.4 chromite sand, 26 zircon sand, 5.5 potassium feldspar powder, 2.8 borosilicate glass powder, 2.5 high-purity graphite, and 0.8 metallic silicon powder; then prepare a 40% yellow dextrin aqueous solution according to 3.5% of the total mass of the above mixture; then start the mixing tank, add chromite sand and zircon sand first, then add yellow dextrin aqueous solution, and stir for 3 minutes; then add potassium feldspar powder and borosilicate glass powder to the mixing tank, then add high-purity graphite and metallic silicon powder, and continue stirring for 30 minutes to complete granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 2 hours to complete drying, and obtain dense sealing layer granules; (2) Prepare the raw materials for the weakly bonded transition layer according to the following weight proportions: 65 zircon sand, 26 low-chromium magnesia sand, 3.5 potassium feldspar powder, 2.0 borosilicate glass powder, 2.5 high-purity graphite, 0.7 silicon metal powder, and 0.3 polypropylene fiber (i.e., organic fiber); then prepare water-based resin according to 3% of the total mass of the above mixture; next, start the mixing tank, add zircon sand and low-chromium magnesia sand first, then add water-based resin, and stir for 3 minutes; then, add potassium feldspar powder and borosilicate glass powder to the mixing tank, then add high-purity graphite, silicon metal powder and polypropylene fiber, and continue stirring for 30 minutes to complete granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 2 hours to complete drying, and obtain the weakly bonded transition layer granules; (3) Prepare the raw materials for the loose support layer according to the weight parts, including: 98.5% high-purity fused magnesia and 1.5% high-purity graphite; then prepare water-based resin according to 3% of the total mass of the above mixture; then start the mixing tank, add the high-purity fused magnesia first, then add the water-based resin, and stir for 3 minutes; then add the high-purity graphite into the mixing tank and continue stirring for 30 minutes to complete the granulation; finally, transfer the material in the mixing tank to a drying drum at 200-250℃, keep it in an air atmosphere for 1 hour to complete the drying and obtain the loose support layer granules. (4) such as Figure 1 As shown, the aforementioned granular material is sequentially laid at the bottom of the ladle, forming a loose support layer, a weakly bonded transition layer, and a dense sealing layer, respectively. The loose support layer accounts for 30% of the total height of the diversion sand, the weakly bonded transition layer accounts for 50%, and the dense sealing layer accounts for 20%.
[0033] (5) Conduct industrial trials: 500 heats were tested on a 200-ton ladle at a steel plant to smelt high-oxygen steel, with an average waiting time of 45 minutes.
[0034] The experimental results are as follows: 14 furnaces did not self-start, resulting in a self-start rate of 97.2%. During the casting process, Comparative Example 1 exhibited a higher number of furnaces showing a "lag" phenomenon, indicating poor sintering of its sintered layer. Scanning electron microscopy (SEM) analysis revealed that the three-layer guiding sand system of Comparative Example 1 lacked inert microspheres as stress concentration points, resulting in an overly homogeneous structure that hindered crack initiation. According to fracture mechanics principles, this homogeneous structure requires higher energy (i.e., a greater casting start-up pressure) to induce cracking.
[0035] Comparative Example 2: Commercially available mainstream chromium-based drainage sand was selected.
[0036] The results of the industrial test are as follows: out of 500 furnaces, 25 furnaces did not self-start, the self-start rate was 95.0%, the sintered layer structure was uneven, sometimes over-fired and sometimes under-fired, and the self-start rate fluctuated greatly.
[0037] The following is a comparison table of experimental results data between Examples 1-3 and Comparative Examples 1-2: Note: "Standard deviation of self-opening rate" is an indicator for measuring the volatility of the performance of the diversion sand. To assess the product's stability, the test data from 500 heats were divided into 10 groups (50 heats per group) in chronological order, and the self-opening rate was calculated for each group. Then, the standard deviation of the self-opening rate data for these 10 groups was calculated. The calculation formula is: Where n = 10 (number of groups), x i Let i be the self-opening rate of the i-th group. The total self-opening rate is given. The results show that the standard deviation σ of the product of this invention is <0.1%, indicating that its performance is highly stable and exhibits minimal fluctuations during long-term use.
[0038] "Post-firing structural stability" refers to the performance consistency of the priming sand from different production batches (50 furnaces) under the same test conditions.
[0039] Example 4: In this embodiment, when preparing the weakly bonded transition layer granules, the inert microspheres are spherical zirconia microspheres with a weight ratio of 2 parts, and the rest are the same as in Example 1.
[0040] Industrial trials were conducted: 500 heats were tested on a 250-ton ladle at a steel plant, smelting specialty steels, with an average waiting time of 65 minutes.
[0041] The results of the industrial test are as follows: out of 500 furnaces, 4 furnaces did not start automatically, resulting in a self-start rate of 99.2%.
[0042] The results of the examples show that even under extreme conditions such as higher static pressure of molten steel (250-ton ladle) and longer thermal action time (average waiting time of 65 minutes), the diversion sand described in this invention can still maintain an extremely high self-opening rate. This fully demonstrates that its unique "gradient sintering layer" structure can effectively resist the long-term penetration of high-temperature molten steel and static pressure, preventing the formation of over-sintering or "cold steel" layers; at the same time, the "micro-valve effect" ensures that low-stress start-up can still be achieved under extremely high static pressure. Therefore, this invention expands the application range of high-performance diversion sand and is well-suited for large and extra-large ladles and long-process smelting processes with extremely high self-opening requirements. The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A high self-opening rate drainage sand based on gradient sintering and micro-valve effect, characterized in that: It includes a dense sealing layer, a weakly bonded transition layer, and a loose maintaining layer arranged sequentially; The dense sealing layer comprises the following raw materials in parts by weight: 50-70 parts chromite sand, 20-30 parts zircon sand, 5-8 parts potassium feldspar powder, 2-4 parts borosilicate glass powder, 2-3 parts high-purity graphite, and 0.5-1 parts metallic silicon powder. The weakly bonded transition layer comprises the following raw materials in parts by weight: 50-70 zircon sand, 20-30 low-chromium magnesia sand, 3-5 potassium feldspar powder, 2-3 borosilicate glass powder, 1-3 inert microspheres, 2-3 high-purity graphite, 0.5-1 metallic silicon powder, and 0.1-0.5 organic fibers. The loose support layer comprises the following raw materials in parts by weight: 97-99 parts high-purity fused magnesia and 1-3 parts high-purity graphite.
2. The high self-opening rate drainage sand based on gradient sintering and micro-valve effect according to claim 1, characterized in that: The chromite sand contains Cr2O3≥45%, zircon sand ZrO2≥65%, low-chromium magnesia MgO≥90%, high-purity fused magnesia MgO≥99.50%, and high-purity graphite C≥99.99%.
3. The high self-opening rate drainage sand based on gradient sintering and micro-valve effect according to claim 1, characterized in that: The potassium feldspar powder has a particle size of 200 mesh, the borosilicate glass powder has a particle size of 200 mesh, the high-purity graphite has a particle size of 1000 mesh, the metallic silicon powder has a particle size of 200 mesh, the high-purity fused magnesia has a particle size of 20-180 mesh, and the organic fiber has a length of 1-3 mm.
4. The high self-opening rate drainage sand based on gradient sintering and micro-valve effect according to claim 1, characterized in that: The inert microspheres are spherical or near-spherical structures made of zirconium oxide, corundum, or boron nitride, with a Mohs hardness greater than 7 and a particle size of 0.5-1 mm.
5. A method for preparing high self-opening rate drainage sand based on gradient sintering and micro-valve effect according to any one of claims 1-4, characterized in that, Includes the following steps: The first step involves preparing granular materials for a dense sealing layer, a weakly bonded transition layer, and a loose maintaining layer, specifically as follows: (1) Preparation of dense sealing layer granules: Prepare chromite sand, zircon sand, potassium feldspar powder, borosilicate glass powder, high-purity graphite and metallic silicon powder according to the corresponding proportions, and then prepare a yellow dextrin aqueous solution with a mass fraction of 40-45% according to 3-4% of the total mass of the above mixture; then, start the stirring tank, first add chromite sand and zircon sand, then add yellow dextrin aqueous solution, and stir for 3 minutes; Next, potassium feldspar powder and borosilicate glass powder are added to the mixing tank, followed by high-purity graphite and metallic silicon powder. The mixture is stirred continuously for 30 minutes to complete granulation. Finally, the material in the mixing tank is transferred to a drying drum at 200-250°C and kept in an air atmosphere for 1-2 hours to complete drying. (2) Preparation of weakly bonded transition layer granules: Prepare zircon sand, low-chromium magnesia sand, potassium feldspar powder, borosilicate glass powder, inert microspheres, high-purity graphite, metallic silicon powder, and organic fiber according to the corresponding proportions. Then, prepare water-based resin according to 2.5-3.5% of the total mass of the above mixture. Next, start the mixing tank, add zircon sand and low-chromium magnesia sand first, then add water-based resin, and stir for 3 minutes. Next, potassium feldspar powder and borosilicate glass powder are added to the mixing tank, followed by inert microspheres, high-purity graphite, metallic silicon powder and organic fiber. The mixture is stirred for 30 minutes to complete granulation. Finally, the material in the mixing tank is transferred to a drying drum at 200-250°C and kept in an air atmosphere for 1-2 hours to complete drying. (3) Preparation of loose maintenance layer granules: Prepare high-purity fused magnesia and high-purity graphite in the appropriate proportion, and then prepare water-based resin at 2.5-3.5% of the total mass of the above mixture; then, start the mixing tank, add high-purity fused magnesia first, then add water-based resin, and stir for 3 minutes. Next, high-purity graphite is added to the mixing tank and stirred continuously for 30 minutes to complete granulation. Finally, the material in the mixing tank is transferred to a drying drum at 200-250°C and kept in an air atmosphere for 1-2 hours to complete drying. The second step involves laying the granular material obtained in step one at the bottom of the ladle, forming a loose maintenance layer, a weakly bonded transition layer, and a dense sealing layer, respectively. The loose maintenance layer accounts for 30% of the total height of the diversion sand, the weakly bonded transition layer accounts for 50% of the total height of the diversion sand, and the dense sealing layer accounts for 20% of the total height of the diversion sand.